Changing Senario in Indian Technical and Vocational Systems in 20005 Strategies for the Management of Change - Jain, P. C.; Tiwari, N. P. (Journal of Engineering Education Transformations, 1991)
Hundreds of research institutions all over the world are busy in conducting fundamental and applied researches in science and technology. The rate of development is exponential. Newer and high Technologies are being evolved everyday. Rapid developments in science and technology have influenced the total environment. This has forced a/l the systems and the sub-systems to change and adjust with the emerging environment. "Management of Change" has become the talk of today.